AN ANALYSIS OF GRAMMATICAL ERRORS IN THE SKRIPSI DISCUSSION OF EFL STUDENTS - Asrifi Maula; Mutmainnah Mustofa; Imam Wahyudi Karimullah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: Many EFL students produce many errors in their writing regarding grammatical aspect. The previous study focused on grammatical errors for EFL students but in different places and levels of student’s written text. And the result showed that the students had difficulties in using English grammar both of written and oral.This present study aims to analyze the most dominant errors made by the last semester students of English department of University of Islam Malang on their thesis especially in the part of discussion.This study was designed to be descriptive qualitative method. The data were collected by simple random sampling from some of skripsi discussion made by EFL students of University of Islam Malang in the last two years 2018 and 2019. The researcher took from the library of FKIP UNISMA Malang. Then, the researcher analyzed based on the steps of errors analysis. The steps were identification, classification and description of errors by using tabulation.Furthermore, the researcher followed the error analysis procedures to analyze the data. Moreover, the errors were classified into surface strategy taxonomy theory as proposed Dulay et al. the result shows that the most dominant errors were misformation 34 (40%) followed by omission 33 (38.83%), misordering 10 (11.77%), and addition 8 (9.42%) so, the total errors from the skripsi discussion were 85 errors. The current study investigated that the causes of errors were inter-lingual interference.Based on the result of this study, the researcher found that the students still have problem with understanding their English grammar rules to their writing process. Therefore, the researcher suggested for the EFL students to pay attention in the term of using grammar rule on their written text or oral and be aware to increase their knowledge about English grammar correctly. For the lectures, the researcher also suggested to pay more attention to students grammatical errors in their writing. And the last, for the future researcher, the researcher suggested to conduct the deeper study of grammatical error not only in the skripsi discussion but also in the whole written English at a higher level of students. Keywords: Grammatical errors, skripsi discussion, omission, addition, misformation, misordering.